Respuesta :

[tex]\implies {\blue {\boxed {\boxed {\purple {\sf { \frac{( {a}^{2} + {b}^{2} )}{a} }}}}}}[/tex]

[tex]\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\red{:}}}}}[/tex]

[tex] \frac{ {a}^{4} - {b}^{4} }{ {a}^{3} - a {b}^{2} } [/tex]

[tex] \\= \frac{ ({ {a}^{2} })^{2} - { ({b}^{2} })^{2} }{a( {a}^{2} - {b}^{2} )} [/tex]

[ ∵ (a²)² = [tex]{a}^{4}[/tex] ]

[tex] \\= \frac{( {a}^{2} + {b}^{2} )( {a}^{2} - {b}^{2}) }{a( {a}^{2} - {b}^{2}) } [/tex]

[tex] \\= \frac{( {a}^{2} + {b}^{2} )}{a} [/tex]

Note:

[tex] {a}^{2} - {b}^{2} = (a + b)(a - b)[/tex]

[tex]\large\mathfrak{{\pmb{\underline{\orange{Mystique35 }}{\orange{ヅ}}}}}[/tex]

ACCESS MORE